THEORETICAL CONSTRUCTION OF THE STABILITY OF THE STOCK MARKET - GONGALO, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The stock market quite justifiably refers to the most volatile varieties of the financial market. First of all, this is due to the high sensitivity of the state of the stock market to the external environment in its wide manifestation, not limited to the economic plane. In turn, this leads to the emergence of internal imbalances, which leads to disruption of market stability and possible diffusion to other sectors of the economy. This justifies the relevance of stock market stability research at the theoretical, methodological and applied levels.The article is devoted to the research and systematization of the scientific position regarding the economic content of the concept of stock market stability and the construction of its theoretical construct. The characteristics of scientific views on the nature of instability in the financial sector of the economy in terms of proto-theories, pro-cyclical theories and adaptive theories are presented. The scientific approaches to the study of financial stability in terms of reverse and direct approaches are disclosed. The main substantive emphases of the theories of behavioral finance and financial networks from the standpoint of ensuring the stability of the stock market are substantiated. The interpretation of the economic content of the concept of the stock market is developed from the standpoint of the methodological apparatus of theories of behavioral finance and financial networks. The theoretical construct of the concept of stability of the stock market is formed according to the functional approach, namely, the stability of the stock market is proposed to be interpreted as its ability to continuously and qualitatively perform the main functions in a dynamic and asymmetric environment, which is ensured by preventing the accumulation of destructive internal (market) imbalances and the materialization of risks, monitoring and control over the nature of network relations between market participants, their ability to absorb the negative impact of shocks and not generate systemic risks. The signs of the stability of the stock market are outlined from the standpoint of its main functions, which include: the investment function, the function of redistribution of ownership rights to capital, as well as the movement of capital between economic sectors, the function of redistribution of risks associated with investment, as well as the function of financing the state budget.
Keywords: stock market; functions; stock market stability; financial stability